Daptomycin-Resistant Enterococcus faecalis Diverts the Antibiotic Molecule from the Division Septum and Remodels Cell Membrane Phospholipids - Truc T. Tran (American Society for Microbiology, 2013)
ABSTRACT Treatment of multidrug-resistant enterococci has become a challenging clinical problem in hospitals around the world due to the lack of reliable therapeutic options. Daptomycin (DAP), a cell membrane-targeting cationic antimicrobial lipopeptide, is the only antibiotic with in vitro bactericidal activity against vancomycin-resistant enterococci (VRE). However, the clinical use of DAP against VRE is threatened by emergence of resistance during therapy, but the mechanisms leading to DAP resistance are not fully understood. The mechanism of action of DAP involves interactions with the cell membrane in a calcium-dependent manner, mainly at the level of the bacterial septum. Previously, we demonstrated that development of DAP resistance in vancomycin-resistant Enterococcus faecalis is associated with mutations in genes encoding proteins with two main functions, (i) control of the cell envelope stress response to antibiotics and antimicrobial peptides (LiaFSR system) and (ii) cell membrane phospholipid metabolism (glycerophosphoryl diester phosphodiesterase and cardiolipin synthase). In this work, we show that these VRE can resist DAP-elicited cell membrane damage by diverting the antibiotic away from its principal target (division septum) to other distinct cell membrane regions. DAP septal diversion by DAP-resistant E. faecalis is mediated by initial redistribution of cell membrane cardiolipin-rich microdomains associated with a single amino acid deletion within the transmembrane protein LiaF (a member of a three-component regulatory system [LiaFSR] involved in cell envelope homeostasis). Full expression of DAP resistance requires additional mutations in enzymes (glycerophosphoryl diester phosphodiesterase and cardiolipin synthase) that alter cell membrane phospholipid content. Our findings describe a novel mechanism of bacterial resistance to cationic antimicrobial peptides. IMPORTANCE The emergence of antibiotic resistance in bacterial pathogens is a threat to public health. Understanding the mechanisms of resistance is of crucial importance to develop new strategies to combat multidrug-resistant microorganisms. Vancomycin-resistant enterococci (VRE) are one of the most recalcitrant hospital-associated pathogens against which new therapies are urgently needed. Daptomycin (DAP) is a calcium-decorated antimicrobial lipopeptide whose target is the bacterial cell membrane. A current paradigm suggests that Gram-positive bacteria become resistant to cationic antimicrobial peptides via an electrostatic repulsion of the antibiotic molecule from a more positively charged cell surface. In this work, we provide evidence that VRE use a novel strategy to avoid DAP-elicited killing. Instead of “repelling” the antibiotic from the cell surface, VRE diverts the antibiotic molecule from the septum and “traps” it in distinct membrane regions. We provide genetic and biochemical bases responsible for the mechanism of resistance and disclose new targets for potential antimicrobial development.